From Cultural Performance to Social Learning: Rethinking Traditional Performing Arts in Contemporary Indonesia - Muhammad Nur Salim; Muhamad Ainun Zibran (Gema Cendekia Institute, 2026)
Traditional performing arts have commonly been examined as forms of cultural heritage, while their role as social learning environments remains underexplored. This study investigates how Wayang Kulit, Ketoprak, and Ludruk function as mechanisms of social learning and cultural knowledge transmission in contemporary Indonesia. Using a qualitative literature review approach, data were collected from scholarly publications addressing social learning, cultural transmission, community learning, and traditional performing arts. The analysis employed thematic analysis to identify recurring learning processes embedded within performative practices. The findings indicate that traditional performing arts facilitate three complementary forms of learning: observational learning through moral modelling in Wayang Kulit, participatory learning through collective engagement in Ketoprak, and critical learning through social critique in Ludruk. These processes contribute to the transmission of cultural knowledge, the formation of individual and collective identities, and the strengthening of cultural resilience. Based on these findings, the study proposes the Traditional Performing Arts Social Learning Ecosystem (TPSLE) framework, which conceptualizes traditional performances as community-based learning systems that sustain cultural continuity while adapting to social change.